2016
DOI: 10.1053/j.gastro.2016.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Polycomb Repressive Complex 2 From Mouse Intestine Causes Loss of Stem Cells

Abstract: In intestinal tissues of mice, PRC2 maintains small intestinal stem cells by promoting proliferation and preventing differentiation in the intestinal stem cell compartment. PRC2 controls gene expression in multiple signaling pathways that regulate intestinal homeostasis. Sequencing data are available in the genomics data repository GEO under reference series GSE81578; RNA sequencing data are available under subseries GSE81576; and ChIP sequencing data are available under subseries GSE81577.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
89
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(100 citation statements)
references
References 42 publications
(41 reference statements)
7
89
1
Order By: Relevance
“…The enzymatic activity of this complex mediates the trimethylation of lysine 27 on histone H3 (H3K27me3) and leads to transcriptional repression of target genes (38,39). In a recently reported study, EED was found to regulate intestinal homeostasis, and EED KO mice showed defects in stem cell proliferation and lineage differentiation in the steady state (22,24). This phenotype makes this mouse model impractical for studying the role of PRC2 in colitis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The enzymatic activity of this complex mediates the trimethylation of lysine 27 on histone H3 (H3K27me3) and leads to transcriptional repression of target genes (38,39). In a recently reported study, EED was found to regulate intestinal homeostasis, and EED KO mice showed defects in stem cell proliferation and lineage differentiation in the steady state (22,24). This phenotype makes this mouse model impractical for studying the role of PRC2 in colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Such epithelial defects were detected in EED-depleted mice, but not in EZH2 KO mice, an effect likely due to the functional redundancy between EZH2 and EZH1 (24). However, EZH2 has higher enzymatic activity than EZH1 and is more frequently dysregulated in tumors compared with other components of PRC2, suggesting some unique functional properties (24). Interestingly, a study applying a rank-based expression profile comparative algorithm between UC patients and siRNA-treated cells identified EZH2 as one of the top candidates for involvement in IBD (25).…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…Accordingly, DNA methylation patterns are very similar between adult ISCs and terminally differentiated enterocytes (1012). Loss of essential components of the Polycomb Repressive Complex 2, which positions the H3K27me3 mark, in the adult ISCs leads to cell cycle arrest and spontaneous differentiation towards the secretory lineage, yet has little effect on enterocyte specific differentiation program (1315). Consistently, H3K27me3 patterns are very similar between adult ISCs and enterocytes (14).…”
Section: Introductionmentioning
confidence: 99%